Management Conference Report Organizational Neurotics - del Bueno, Dorothy (Operating Room Nurses Association of Canada Journal, 1992)
Health care organizations are in a survival mode. Due to ﬁscal cutbacks, political insensitivity and a public that’s demanding greater accountability in all spheres of health care, management personnel are being coerced into initiating drastic changes. These changes or shifts in paradigms have the potential to make organizations listless, becalmed and de- pressed, says Dr. Dorothy del Bueno, one of the keynote speakers at the recent Health Conference '92, sponsored by the B.C. Health Association, and the Registered Nurses Association of B.C., held in Vancouver in mid-November.